THE CONCEPT OF FAMILY RESILIENCE TOWARDS THE ISSUE OF INFIDELITY IN HOUSEHOLDS: Analysis of the Hadith al-Ifki - Is, Fadhilah; Harahap, Alwi Padly; Eddien Sharief, Manal Mohey (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2025)
The issue of infidelity in a household is one of the serious problems that can damage family harmony. One approach to understanding family resilience to this crisis is through the concept of family resilience, which refers to the family’s ability to overcome challenges and maintain its integrity. The hadith al-Ifki, which tells of the slander against ‘Aisha and her reaction to the accusation, provides valuable insight into how family resilience can be built in severe trials. This study aims to analyze the application of family resilience to the issue of infidelity in a household based on the perspective of the hadith al-Ifki. The method used is literature analysis with a qualitative approach, examining the sources of hadith and the interpretations of scholars regarding al-Ifki and its relevance in the context of modern families. The results of the study show that the Prophet. Showed that very relevant problem-solving strategies, such as collective confidence, problem anatomy, problem identification, open communication, and family support, can be a foundation for families in dealing with the problem of infidelity. In conclusion, the application of the concept of family resilience based on the hadith al-Ifki can help families face the challenges of the issue of infidelity while maintaining family harmony and dignity.